UTILIZACION DE ESPECIES AUTOCTONAS PARA RECUPERACION DE SUELOS DEGRADADOS ENMENDADOS CON LODOS RESIDUALES - GASCÓ, G.; ALONSO, J.; MARTINEZ IÑIGO, M. J.; LOBO, M. C. (III Congreso Forestal Español, 2001)
The objective of this study was to analyse if composted sewage sludges could be used to amend degraded soils. Two different treatments were applied to Nerium oleander L. and Quercus ilex L (120 Tons/Ha. y 60 Tons/Ha) in a greenhouse with controled conditions. Both heavy metals and nutrients soil contents were analysed to study the influence of the compost in soil properties. Moreover, the effect of the residue in physiological and nutritive plants properties were evaluated.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español pub-location: Granada
Keywords: composted sewage sludge; degraded soils; Heavy metals; Nerium oleander L.; Quercus ilex L.

UTILIZACION DE ESPECIES AUTOCTONAS PARA RECUPERACION DE SUELOS DEGRADADOS ENMENDADOS CON LODOS RESIDUALES - GASCÓ, G; ALONSO, J; MARTINEZ IÑIGO, M J; LOBO, M C (III Congreso Forestal Español, 2001)
The objective of this study was to analyse if composted sewage sludges could be used to amend degraded soils. Two different treatments were applied to Nerium oleander L. and Quercus ilex L (120 Tons/Ha. y 60 Tons/Ha) in a greenhouse with controled conditions. Both heavy metals and nutrients soil contents were analysed to study the influence of the compost in soil properties. Moreover, the effect of the residue in physiological and nutritive plants properties were evaluated.
Keywords: composted sewage sludge; degraded soils; Heavy metals; Nerium oleander L.; Quercus ilex L.